Adsorption Desorption of Chromium (III) Ion on Cellulose from Wood Powder - Risfidian Mohadi; Nurlisa Hidayati; Aldes Lesbani (Chemical Engineering Diponegoro University, 2014)
This study of adsorption desorption of chromium ion on cellulose from wood powder has been carried out systematically and also wood powder was used as adsorbent control in this research. Adsorption process was studied through investigation of adsorption time and variation of chromium ion in the adsorption. Desorption process was investigated using several desorption reagents such as hydrochloric acid, ammonium acetate, sodium EDTA, and water. Data of adsorption time of chromium ion on cellulose and wood powder was calculated to obtain adsorption rate constant of chromium ion. Then the data of variation concentration of chromium was formulated to obtain adsorption capacity of chromium ion on cellulose and wood powder. The results showed that adsorption rate constant of chromium on cellulose is 0.007 min-1 and 0.002 min-1 for wood powder. Adsorption capacity of chromium ion on cellulose is higher than on wood powder while 76.92 mol/g for cellulose and 55.56 mol/g for wood powder. The results of desorption using various desorption shows sodium EDTA is appropriate reagent for desorption of chromium ion on both cellulose and wood powder. Keywords - adsorption, cellulose, chromium, desorption.